SPECULATIVE DESIGN METHOD AS AN ADVANCED TECHNOLOGY FOR CREATING FUTURE SCENARIOS - Nishonov Nodir Alimjanovich (Bright Mind Publishing, 2025)
On June 28, 2024, at a videoconference meeting chaired by President Shavkat Mirziyoyev, dedicated to the review of work in the field of youth policy, discussion of new tasks and proposals, he touched upon the issues of developing the existing higher education system in our country, and noted that further increasing the scientific potential of higher education institutions, expanding the scope of training scientific and scientific-pedagogical personnel are among the most important issues. Therefore, today, great importance is attached to the development of our country's education system, its harmonization with the requirements of the times. In this regard, it is important that the system of training specialists, education and knowledge provision is closely linked to the requirements of reforms. This article will discuss the speculative design method that increases the quality and efficiency of future personnel.
Keywords: Scenario, futurology, speculative design, modular lessons, project approach, multidisciplinary approach, seminar lessons, brainstorming, design fiction, speculative prototyping, systems thinking.